ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU - Syarifudin, Akhmad (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2015)
This study aims to determine the quantity of EOQ's economical raw material ordering in each order to achieve inventory cost efficiency and to find out the reorder point of bread making raw materials. The method of calculating the raw material inventory applied by the bread company CV Hasanah Gombong can be seen by purchasing raw materials, using raw materials, ordering costs, storage costs, and calculating total inventory costs.